2023
DOI: 10.17344/acsi.2022.7885
|View full text |Cite
|
Sign up to set email alerts
|

Novel Antioxidants Based on Selected 3d Metal Coordination Compounds with 2-Hydroxybenzaldehyde 4,S-Diallylisothiosemicarbazone

Abstract: 2-Hydroxybenzaldehyde 4,S-diallylisothiosemicarbazone (HL) was synthesized and characterized by 1H, 13C NMR and FTIR spectroscopies. It exists in solution in two isomeric forms: cis (~25%) and trans (~75%). Six stable complexes were obtained by interaction of HL with copper(II), nickel(II), cobalt(III) and iron(III) salts: [Cu(L)Cl] (1), [Cu(L)NO3] (2), [Cu(3,4-Lut)(L)NO3] (3), [Ni(L)OAc] (4), [Co(L)2]Cl (5), [Fe(L)2]NO3 (6). The synthesized complexes have been studied by elemental analysis, FTIR, molar electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 26 publications
(39 reference statements)
0
2
0
Order By: Relevance
“…The elemental analysis was performed similarly to the literature procedures [50] and on the automatic Perkin Elmer 2400 elemental analyzer. R-38 rheochord bridge was used to measure the resistance of 1 mM methanol solutions of complexes 1-6 at 20 • C. At the first step, the allyl iodide (1.68 g, 10.0 mmol) has been added to the solution of N 4 -allylthiosemicarbazide (1.31 g, 10.0 mmol) in ethanol [51]. After 2 h of stirring at room temperature, 2-formylpyridine (1.07 g, 10.0 mmol) was added.…”
Section: Compoundmentioning
confidence: 99%
“…The elemental analysis was performed similarly to the literature procedures [50] and on the automatic Perkin Elmer 2400 elemental analyzer. R-38 rheochord bridge was used to measure the resistance of 1 mM methanol solutions of complexes 1-6 at 20 • C. At the first step, the allyl iodide (1.68 g, 10.0 mmol) has been added to the solution of N 4 -allylthiosemicarbazide (1.31 g, 10.0 mmol) in ethanol [51]. After 2 h of stirring at room temperature, 2-formylpyridine (1.07 g, 10.0 mmol) was added.…”
Section: Compoundmentioning
confidence: 99%
“…Copper, nickel, cobalt, and iron complexes with 2-hydroxybenzaldehyde 4,S-diallylisothio semicarbazone demonstrated a potent antioxidant activity 14,15 . It was found that highly active 2-hydroxybenzaldehyde-4-allyl-S-methylisothiosemicarbazone complexes with Cu(II), Co(III), Fe(III), and Cr(III) displayed multiple biological activities, Cr(III), Fe(III), and Co(III) complexes demonstrating remarkable antioxidant effect exceeding that of Trolox 16 , while N4,S-diallylisothiosemicarbazones copper(II) coordination compounds having a better antiradical activity than trolox 17 .…”
Section: Introductionmentioning
confidence: 99%